The effect of mouth rinses on surface micro hardness of two esthetic restorative materials - kanan, Sabiha; mohammed, Amaal (Iraqi National Journal of Nursing Specialties, 2012)
Objective: To evaluate the effect of mouth rinses (Biofresh and ZAK) on the surface micro hardness of two light cure restorative material (Tetric ceram ivoclar-vivadent) and (3M Z 250) dental composite. Methodology: The microhardness values of (sixty) composite specimens were measured at the top surfaces after 24 hours of immersion in different solutions (Biofresh, Zak mouth wash and distilled water as control). Comparison done using descriptive statistics (mean, SD, SEM, minimum and maximum values) and inferential statistics (ANOVA and LSD) test. Results: The biofresh mouth rinse which has high alcohol containing has less effect on microhardness of tetric ceram than the zak &distiled water , while the effect of Zak mouth rinse on microhhybrid composit (3M Z250) is less than biofresh &distiled water, also there was highly significant difference between subgroup of tetric ceram and the same for (3M Z250) composite & the effect of the mouth rinse on hardness was material dependent it may be attributed to the differences in chemical composition and filler type of each material. Since it was found that alcohol is not the only factor that has the softening effect on the restorative material, other ingredient in a mouth rinse. may have softening effect on polymer matrix. Recommendations: We recommend for a comparison of color stability for restorative material under the effect of mouth rinsing.